Migration, Communication and Interaction: The Problem of Socialization in Return Migrants (Revista Rupturas, 2025)
This research explores the phenomenon of communicative interaction in return migrants between Mexico and the United States based on the interaction and socialization problems that arise in the process of social reintegration between return migrants and people who are not. This is done through Erving Goffman's theory. The particular case of a Mexican return migrant from Tapalpa, Jalisco, Mexico is analyzed. It is concluded that there are certain aspects that can be classified as a socialization problem, such as language and personal aspects that were modified during the migration process and then reappropriated in the period of return migration.
Keywords: communication; interaction; return migrants; socialization; social dramaturgy